Effect of ownership structure on dividend payments: Evidence from public companies in Nordic and Baltic Countries - Vilija Alekneviéciençe; Karolina Vilimaitçe (Cogent Economics & Finance, 2023)
We investigate whether ownership structure influences the likelihood and amount of dividend payments in two groups of European Union's public companies: Nordic and Baltic. Nordic and Baltic capital markets have become increasingly integrated through Nasdaq OMX stock exchanges and harmonized by the EU corporate governance directives. However, some differences in the corporate governance system, legislation, practice, and ownership structure still exist. The study covers Nordic and Baltic companies listed on the Nasdaq OMX for the period 2013-2020. Logit and Tobit panel regressions are applied to disclose the effect of ownership structure on the likelihood and amount of dividend payments accordingly. We find that ownership concentration positively influences the likelihood and amount of dividend payments in Nordic public companies. Managerial ownership does not influence the likelihood of dividend payments but positively influences their amount. Institutional ownership does not influence the likelihood of dividend payments but negatively influences their amount. Our findings revealed that ownership structure does not have any effect either on the likelihood of dividend payments or on their amount in Baltic public companies. We disclosed that the effect of ownership structure on dividend payments is influenced by the context behind ownership structure. The results of our research will improve understanding and predict the decision-making on dividend payments and will help investors manage their portfolios, choosing between current and future consumption.
Keywords: 330; dividend payments; institutional ownership; managerial ownership; ownership concentration; ownership structure